Role of Integrins in Regulating Proteases to Mediate Extracellular Matrix Remodeling - Yue, Jiao (Springer Netherlands, 2012)
The extracellular matrix (ECM) is an extracellular scaffold composed of complex mixtures of proteins that plays a pivotal role in tumor progression. ECM remodeling is crucial for tumor migration and invasion during the process of metastasis. ECM can be remodeled by several processes including synthesis, contraction and proteolytic degradation. In order to cross through the ECM barriers, malignant cells produce a spectrum of extracellular proteinases including matrix metalloproteinases (MMPs), serine proteases (mainly the urokinase plasminogen activator (uPA) system) and cysteine proteases to degrade ECM components. As major adhesion molecules to support cell attachment to ECM, integrins play critical roles in tumor progression by enhancing tumor cell survival, migration and invasion. Previous studies have shown that integrins can regulate the expression and activity of these proteases through different pathways. This review summarizes the roles of MMPs and uPA system in ECM remodeling and discusses the regulatory functions of integrins on these proteases in invasive tumors.